From Communal to Individual: Shifting Authorities of Family Dispute Resolution in Minangkabau Society - Arifki Budia Warman,; Elimartati,; Dodon Alfiander,; Ashabul Fadhli,; Wardatun Nabilah, (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2023)
This study aims to explain the shift of authority in resolving family disputes in Minangkabau society. At least three authorities are involved in resolving family issues in Minangkabau: religious authority, represented by leaders with religious knowledge; customary authority, held by leaders with their own laws; and state authority, enforced by judges in court based on laws and regulations. This research is a field study with a socio-legal approach. The study examined Minangkabau households in both rural and urban areas, utilizing questionnaires and in-depth interviews to collect data from individuals involved in household disputes. The data were then reduced, presented and verified. This study found that in addition to using the three long-standing authorities in Minangkabau society, disputants are more likely to use individual authority in resolving their family disputes. The disputants are more likely to resolve their family problems independently without involving religious leaders, customary leaders, or religious court judges. The tendency towards individual authority is more prevalent in urban communities. The strengthening of individual authority coincides with the weakening of the formal institutions of the three authorities in Minangkabau society. The factors contributing to the diminishment of these authorities include modernisation, technological advancements, and digitalisation which incentivises the involved parties to logically settle their disputes for their individual gains and aspirations. Based on the research findings, the current study confirms that the shift in family dispute resolution authority indicates that there has been a shift from extended to core family patterns in Minangkabau society